Study the factors that influence the purchase intention towards Amanah Saham Bumiputera 2 (ASB 2) / Mohd Shahrul Affendy Sharib - Sharib, Mohd Shahrul Affendy (Faculty of Business and Management, 2016)
The main purpose of this study is to study the factors that influences the purchase intention towards Amanah Saham Bumiputera 2 (ASB 2) and refine the theoretical framework of the consumer’s intention to purchase with attitude, perceived behavioral control, financial literacy and knowledge. A descriptive research design was adopted for this study. From the SPSS analysis, it indicates that there are significant relationship between individual’s attitude, perceived behavioral control and knowledge with the purchase intention of ASB 2. However, the finding also shows that there is no significant relationship between financial literacy and purchase intention towards ASB 2. The data was collected from 110 respondents that are customers of ASNB Shah Alam. Next, the findings also stated that perceived behavioral control is the most influencing factor that can influence the purchase intention towards ASB 2. All the findings of this study can be used and improvised in the future in order to get the better results.